HADIS SAHIH, HASAN, DAIF DAN MAUDU’ - Nico Akbar; Muhammad Ali (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Hadith is the second primary source of Islamic law after the Qur'an, making its authenticity critically important. This paper explores the four main categories in hadith classification: sahih (authentic), hasan (good), daif (weak), and mauḍū’ (fabricated), focusing on their definitions, distinguishing features, and implications for religious practice. Sahih and hasan hadiths are considered maqbul (accepted) and can be used as sources of Islamic legal rulings, while daif and mauḍū’ hadiths are categorized as mardud (rejected), though some scholars allow conditional use of weak hadiths in non-legal contexts. The author highlights varying scholarly perspectives, both classical and contemporary, on evaluating the reliability of narrators (sanad) and the content (matan) of hadiths. Particular attention is given to the debate over using weak hadiths for virtues of deeds (fadhā’il al-a‘māl) and the consensus on the prohibition of fabricated hadiths in all aspects of religious life. Employing a descriptive-qualitative analytical approach, this paper emphasizes the necessity for critical literacy among Muslims in recognizing and applying valid hadiths, especially in the digital era prone to widespread misinformation. The study encourages a deeper engagement with mustalah al-hadith (hadith terminology and methodology) as an intellectual and spiritual responsibility, aiming to support the integrity of Islamic teachings through verified prophetic traditions.